Economic feasibility of a dairy property modal with real options - da Costa, Ivan Ribeiro Barreto [UNESP]; Santos, David Ferreira Lopes [UNESP] (My University, 2019)
This article aims to evaluate the economic viability of a modal dairy farm in the region of Mococa, State of São Paulo, Brazil. The motivation of this study is the need to bring more information about sources and value to one of the main chains of Brazilian agribusiness. Although the country has the second largest dairy herd in the world, the country's productivity is 67% lower than the main countries in the world, such as the USA. In fact, there is a reduction in the number of rural producers, especially the small and medium-sized ones. Therefore, a research was carried out that included data extracted from a research with a focus group of the CNA/CEPEA to size the modal profile of a rural property dedicated to dairy farming in an important productive region of the State of São Paulo. Based on Discounted Cash Flow Analysis and the Real Options Theory, considering the option of waiver, it was verified that the current management practices and technology employed restrict the economic viability of the activity. However, when considering best management practices and the use of new technologies already available, economic viability is fully possible, restricting the option of abandonment. The results of this study bring new contributions to the sustainability of this important activity of Brazilian agribusiness, which demonstrates the economic importance of professionalization and investment in technology.
Keywords: Agribusiness; Feasibility; Real options